PENGEMBANGAN BAHAN AJAR IPS BERBASIS KETERAMPILAN SOSIAL UNTUK KELAS IV SEKOLAH DASAR 060912 MEDAN DENAI - Rahmadani Tanjung (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
The research objective is to develop social skills based social studies teaching materials. This study uses a quantitative approach. The type of research is development research (Research And Development / R & D), the steps implemented are (1) Planning and Development, (2) Product Effectiveness. The results of the study show that: (1) Children's understanding of social skills has increased. This can be seen in the results of the pre test and post test conducted by researchers in small groups and large (limited) groups. The results of the small group pre test were 5.2% and the post test was 8%, which meant an increase of 2.8% while for the large group the pre test was 5.97% and the test post was 8%, meaning an increase of 2.1%. (2) the effectiveness of the product gets a good value proven from the three validators for the feasibility aspect, the average score is 3.69 (92%), the feasibility aspect of presenting the average score is 3.23 (80.77%), and the last feasibility aspects, the average score is 3.5 (87.5%). The impact of the use of social studies teaching materials based on social skills can make children learn happily, actively and the learning atmosphere becomes fun and children understand more about social skills.